Tax evasion and the minimum wage - Anikó Bíró; Daniel Prinz; László Sándor (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2020)
Exploiting a change in reporting defaults and the implied audit threat in Hungary, we demonstrate that a substantial portion of employees and the self-employed reporting to earn the minimum wage have much higher earnings in reality. This can be seen from their sharp but temporary jump to the new reporting default, a twofold increase in reported earnings. Consistent with misreporting, the response is concentrated both spatially and by employer and the distribution of covariates around the threshold exhibits anomalies. Requiring individuals reporting to earn the minimum wage to pay higher taxes or ask for explicit exceptions increases reported earnings for some and decreases formal employment for others, suggesting a trade-off for taxation. We formalize the empirical findings in a model of minimum wage taxation where earnings underreporting around the minimum wage would justify a move towards higher taxation of those earnings, more aligned with a prevalent international practice.
Keywords: H26; J31; 330; minimum wage; tax evasion; audit; Hungary